Investigation of the thermal deformation of a chip-scale packaged optical accelerometer. (15th October 2020) - Fang, Weidong; Wang, Chen; Bai, Jian; Chen, Jiaxiao; Yao, Yuan; Lu, Qianbo
Highlights: A preliminary chip-scale packaged design of an optical accelerometer is proposed. The relationship between material properties and thermal deformation is obtained. A guide for the design of accelerometers with high thermal stability is proposed. Abstract: Accelerometers based on optical cavity have a complicated situation of thermal deformation, which significantly influences the measurement results. In order to minimize the thermal drift of the accelerometer, a preliminary multilayer structure package design is proposed. A simplified finite element model of this design is built and further optimized in consideration of boundary conditions to compare the thermal drift of the prototype of the accelerometer. The theoretical calculations of the temperature distribution and structure deformation successfully verify the correctness of the simulation results. The relationships between the material properties and the thermal deformation, as well as the vibration of optical path length are obtained via simulation and theoretical calculation; thus, providing a characteristic formula of the optical path length and the material properties. The relationships can be considered a strong guide for the design of multilayer-structure accelerometers with high temperature stability.